2005
DOI: 10.1016/j.jacc.2005.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carotid Atherosclerosis in Andropausal Middle-Aged Men

Abstract: Middle-aged men with symptoms of andropause, together with absolute or compensated (as reflected by high normal to elevated LH) testosterone deficiency, show increased carotid IMT. These data suggest that normal testosterone levels may offer protection against the development of atherosclerosis in middle-aged men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 40 publications
6
96
3
1
Order By: Relevance
“…Similar results were demonstrated in younger men with T levels < 9.8 nmol/mL. 85 In men aged 73-90 years, TT concentrations were inversely correlated with increased carotid intima media thickness (CIMT). 86 In a prospective analysis in 195 independently living older men, FT levels were inversely related to the mean progression of CIMT after adjustment on the usual cardiovascular risk factors; TT concentration were not.…”
Section: Body Composition and Cardiovascular Healthsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar results were demonstrated in younger men with T levels < 9.8 nmol/mL. 85 In men aged 73-90 years, TT concentrations were inversely correlated with increased carotid intima media thickness (CIMT). 86 In a prospective analysis in 195 independently living older men, FT levels were inversely related to the mean progression of CIMT after adjustment on the usual cardiovascular risk factors; TT concentration were not.…”
Section: Body Composition and Cardiovascular Healthsupporting
confidence: 63%
“…Low T status and metabolic syndrome both appear to be independently associated with increased all-cause and cardiovascular mortality. 28,80,81 Hence, several studies have examined the impact of TT, FT, and SHBG levels on cardiovascular health or atherosclerosis 54,72,[82][83][84][85][86][87] Thus, from the analysis of the large Swedish arm of the cross-sectional Osteoporotic Fractures in Men study (3,014 men aged 69-80 years), Tivesten et al observed that individuals with TT and FT levels within the lowest quartile have an increased odds of lower-extremity peripheral artery disease (i.e., ankle and brachial index < 0.9). 84 Hak et al in the Rotterdam Study have investigated the association of T and FT serum levels with aortic atherosclerosis (i.e., radiographic detection of calcified deposits in the abdominal aorta) among 1,032 nonsmoking men aged 55 year and over.…”
Section: Body Composition and Cardiovascular Healthmentioning
confidence: 99%
“…Carotid artery intima-media thickness, a common marker of clinical and subclinical atherosclerosis, has been shown to be correlated inversely with testosterone levels. [65][66][67] Demirbag et al 68 reported a similar finding by examining the intima thickness of the thoracic aorta in older men. Similarly, in the Rotterdam Study population, Hak et al 69 demonstrated that both bioavailable and total testosterone levels were negatively associated with calcified deposits in the abdominal aorta in men older than 55 years of age.…”
Section: Association Of Low Testosterone With Surrogate Markers Of Atmentioning
confidence: 65%
“…In fact, several in vivo and in vitro studies have suggested that androgens increase expression of proatherogenic factors (Adams et al 1995, McCrohon et al 1999, Ng et al 2003, Nheu et al 2011. In contrast, recent clinical studies have shown that low endogenous testosterone levels are associated with advanced atherosclerosis of the carotid artery in middleaged males and that this association is independent of the traditional cardiovascular risk factors (Muller et al 2004, Makinen et al 2005. Low testosterone level is also associated with poor vasodilation of the brachial artery and is an independent risk factor for endothelial dysfunction in men (Akishita et al 2007).…”
Section: Effects Of Androgens On Vascular Remodelingmentioning
confidence: 99%